2018
DOI: 10.1111/bjop.12297
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between visual search and categorization of own‐ and other‐age faces

Abstract: Young adult participants are faster to detect young adult faces in crowds of infant and child faces than vice versa. These findings have been interpreted as evidence for more efficient attentional capture by own-age than other-age faces, but could alternatively reflect faster rejection of other-age than own-age distractors, consistent with the previously reported other-age categorization advantage: faster categorization of other-age than own-age faces. Participants searched for own-age faces in other-age backg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 42 publications
2
4
0
Order By: Relevance
“…Finding that participants were faster on average to categorize other‐age than own‐age faces and more accurate to recognize own‐age than other‐age faces is consistent with previous studies reporting the other‐age categorization advantage (Craig & Lipp, , ; Johnston et al ., ; Wiese et al ., ) and the OAB (Anastasi & Rhodes, ; Rhodes & Anastasi, ; Wiese et al ., ). Finding that the OAB in the current study was due to participants having a more liberal response criterion and responding with more false alarms for older adult than young adult faces is also consistent with previous research (Rhodes & Anastasi, ).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Finding that participants were faster on average to categorize other‐age than own‐age faces and more accurate to recognize own‐age than other‐age faces is consistent with previous studies reporting the other‐age categorization advantage (Craig & Lipp, , ; Johnston et al ., ; Wiese et al ., ) and the OAB (Anastasi & Rhodes, ; Rhodes & Anastasi, ; Wiese et al ., ). Finding that the OAB in the current study was due to participants having a more liberal response criterion and responding with more false alarms for older adult than young adult faces is also consistent with previous research (Rhodes & Anastasi, ).…”
Section: Discussionsupporting
confidence: 90%
“…Despite this, only a handful of studies have investigated categorization and individuation processes in the context of the OAB. Similar to the other‐race categorization advantage, previous studies have shown an other‐age categorization advantage – faster categorization of other‐age than own‐age faces (Craig & Lipp, , ; Johnston, Kanazawa, Kato, & Oda, ; Wiese, Schweinberger, & Hansen, ). To date, no studies have sought to assess whether the other‐age categorization advantage and the OAB are related (as has been done for the own‐race bias), but one study has attempted to manipulate the degree to which observers engaged in age categorization to examine the influence of this manipulation on the OAB.…”
Section: Introductionmentioning
confidence: 65%
See 2 more Smart Citations
“…First impressions of various personality traits are formed from faces, particularly dominance and trustworthiness 16 , 17 that inform important social decisions from voting to criminal sentencing 18 , 19 . This social information can also influence the way that attention is allocated to faces 20 , 21 and can augment the anger superiority effect. For example, the sex of faces influenced the speed of detecting happy and angry faces in crowds 22 .…”
Section: Introductionmentioning
confidence: 99%